2015
DOI: 10.1021/acsami.5b07529
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Barrier Hybrid Coatings by the Assembly of Novel Poly(vinyl alcohol) and Reduced Graphene Oxide Layers through Cross-Linking with Zirconium Adducts

Abstract: Gas-barrier materials obtained by coating poly(ethylene terephthalate) (PET) substrates have already been studied in the recent literature. However, because of the benefits of using cheaper, biodegradable, and nonpolar polymers, multilayered hybrid coatings consisting of alternate layers of reduced graphene oxide (rGO) nanosheets and a novel high amorphous vinyl alcohol (HAVOH) with zirconium (Zr) adducts as binders were successfully fabricated through a layer-by-layer (LbL) assembly approach. Atomic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Therefore, by reduction of GO to rGO and reduction of interlayer distance from 10 to 4 Å, the diffusivity of molecules can be effectively decreased . In another study, the layer by layer deposition of few layer rGO through electrostatic bond formation (similar to our case) is shown to decrease the oxygen transfer rate (OTR) of poly(ethylene terephthalate) substrates by 95% . In another work, rGO/polyimide films prepared by in situ polymerization showed to decrease the OTR by 93% compared to pure PI films .…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, by reduction of GO to rGO and reduction of interlayer distance from 10 to 4 Å, the diffusivity of molecules can be effectively decreased . In another study, the layer by layer deposition of few layer rGO through electrostatic bond formation (similar to our case) is shown to decrease the oxygen transfer rate (OTR) of poly(ethylene terephthalate) substrates by 95% . In another work, rGO/polyimide films prepared by in situ polymerization showed to decrease the OTR by 93% compared to pure PI films .…”
Section: Introductionmentioning
confidence: 96%
“…Detailed procedure for solvent transport study is reported in our previous study. [13] The gas permeability analysis was done by Lyssy gas permeability tester (L100-5000) Switzerland. Samples with dimensions of 12 cm length, 10 cm breadth, and 1 mm thickness were used.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Gas-barrier materials obtained by incorporating various nano fillers have also been well studied by various researchers. [13][14][15] MWCNT can be considered as an ideal reinforcing material which can advance the barrier properties of polymers. [16][17][18][19] Sensing materials have become one of the emerging areas in material science due to their amazing applications in industry, biomedical, and environmental fields.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, scientists have studied ways of improving the oxygen barrier property of the polymer. Some of the methods that have recently been studied in controlling oxygen permeability include crystallization or crosslinking, using side‐chain liquid crystalline polymers or introducing a substance that could react with the permeating gas, or using filler to complicate the path, namely, gas permeation retardation . Especially, research works have been carried out to reduce the oxygen permeability of the polymer matrix up to 80% by using a complex method of controlling crystallization and crosslinking with modified nanofillers …”
Section: Introductionmentioning
confidence: 99%